14:40-15:10 Immune clockwork in healthy an pathological pregnancies - Gaudilliere, Brice (Journal of reproductive immunology, 2023)
Pre-term birth and preeclampsia are the leading cause of maternal mortality and morbidity worldwide. However, our ability to predict these severe pregnancy complications is limited. Dysregulation of pregnancy-induced immune adaptions are increasingly implicated in the pathogenesis of PTB and PE. As such, understanding of the mechanisms that drive the normal feto-maternal immune adaptations during pregnancy is a necessary first step to identifying biomarkers for the prediction and prevention of PTB and PE. In recent studies of healthy pregnancies, we described the chronology of immune system, proteomic, and metabolomic adaptations occurring in the maternal blood during pregnancy. Here, I will present ongoing work in our laboratory using a multi-omic systems immunology approach leveraging high dimensional suspension and imaging mass cytometry to study the local and peripheral immune adaptations during a healthy pregnancy and identify chronological immune dysfunctions predictive of preterm birth and PE